EFFECT OF DIFFERENT SUBSTRATA ON GROWTH, SURVIVAL AND PRODUCTION OF MACROBRACHIUM ROSENBERGII IN POLDERS - RANJEET, K.; KURUP, B. MADHUSOODANA (Journal of the Inland Fisheries Society of India, 2022)
Growth, survival and production performance of Macrobrachium rosenbergii in polders incorporating two different artificial substrates was compared against treatments without any added substrates. Treatments involving tiers of nylon nets as added substrates (T3), the mean weight (58.8g) and survival rate (58.6%) were comparatively better than treatment T2 involving earthen pipes (52.2g and 48.4%) or T1 with no additional substrates (32.5g and 26.8% respectively) at all. Preference of net-tiers during initial phase of development was an important factor governing better production in T3, which was significantly higher (605.6 kg/ha/6months) than T2 or T1 (453.1 and 211.6 kg/ ha/6 months).Keywords : Macrobrachium rosenbergii, polders, Kuttanad, artificial substrate